The plasma density distribution in the inner region of Saturn's magnetosphere. Issue 6 (6th June 2013) - Persoon, A. M.; Gurnett, D. A.; Leisner, J. S.; Kurth, W. S.; Groene, J. B.; Faden, J. B.
Abstract : [1] Electron density measurements derived from the upper hybrid resonance frequency have been obtained from the Cassini Radio and Plasma Wave Science experiment over a 7 year period from 28 October 2004 through 7 November 2011. Additional density measurements inside the orbit of Enceladus and outside the orbit of Rhea have made it possible to expand a previously published density model to radial distances from 2.6 to 10.0 Saturnian radii ( R S ). The distribution of density data is compared to a simple scale height density model for a single‐species plasma within 8° of the magnetic equatorial plane. There is a broad peak in the equatorial density distribution between 4 R S and 5 R S with the plasma falling off both inward and outward from the peak region. The radial dependence of the equatorial density profile varies as R 4.0 from 2.6 R S to 4 R S and as R –4.8 from 5 R S to 10 R S . The plasma distribution outside 5 R S remains consistent with earlier density models but additional density measurements inside 4 R S provide information on the plasma distribution in this inner region that will be the focus of the F‐Ring and proximal orbits near the end of the Cassini mission. Key Points: Simple scale height model of the plasma density is expanded from 2.6 to 10 R_S Equatorial density is modeled by a power‐law equation in radial distance. Equatorial plasma varies as R^4.0 inside 4 R_S and as R^‐4.8 outside 5 R_S